Is a two-tier trauma team activation system the most effective way to manage trauma in the UK?. (October 2013) - Jenkins, P; Kehoe, A; Smith, JE
This review describes the evidence exploring the use of a two-tier trauma team activation system, reviewing the background, history, data available and potential benefits and downsides. The current evidence suggests that a two-tier system may be a lean, cost-effective system, focussed on patient outcome, which could be implemented throughout the UK. Despite its current use in some hospitals, there is limited data from similar systems supporting this in a UK setting. Specific activation criteria need to be validated to ensure appropriate activation of trauma teams, ensuring optimal patient outcome and ensuring best practice.